Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Terhadap Hasil Belajar Kognitif dan Literasi Sains Siswa - Safnowandi, Safnowandi (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2021)
The objectives of this research are to: 1) determine the effect of the Contextual Teaching and Learning (CTL) learning model on cognitive learning outcomes; and 2) to determine the effect of the Contextual Teaching and Learning (CTL) learning model on students' scientific literacy. This type of research is a quasi experiment. The research design of pre-test-post-test non equivalent control group design. The population in this study were all class VII students of SMPN 1 Tanjung North Lombok Regency in the academic year 2017/2018 which consisted of 6 classes. The sampling technique used purposive sampling, in order to obtain class VII 3 as the experimental class and class VII 1 as the control class. The instruments used to collect data were multiple choice questions totaling 20 items to measure student cognitive learning outcomes and essay questions to measure content and the scientific context. Meanwhile, worksheets are used to measure the scientific process. The data analysis technique used two-way ANOVA with a significance level of 0.05% using SPSS 16 for Windows. The results showed that: 1) there was an effect of the application of the Contextual Teaching and Learning (CTL) learning model on cognitive learning outcomes (p <0.05); and 2) there is an effect of the Contextual Teaching and Learning (CTL) learning model on students' scientific literacy (p <0.05).